Relationship Function of Head of Room Management with Nurse Motivation At Faisal Makassar Islamic Hospital - Suryani, Suryani; Hasriany, Hasriany; Rahmat, Sri Wahyuni (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
The management function is a process to finish a job problem consisting of planning, organizing, directing, and controlling. The room’s chief as a leader of the service in inpatient room to be responsible to plan, organizing, directing and controlling the nurses and all of the staffs to give care service with award system to reflect value system of individual and group. The aim of this study is to know the relation of management functions of room’s chief with the motivation of associate nurse at inpatient room in Islam Faisal Hospital Makassar. The type of this research was analytic observational with cross-sectional study approach model with 51 respondents sample. The result of this study indicate there is relation of room’s chief planning with motivation of nurse associate (value p = 0,001), there is no relation of organizing with motivation of nurse associate (p = 0,358), there is relation of directing with motivation of nurse associate (p  = 0,005), there is relation of controlling with motivation of nurse associate (p  = 0.0001)